Cortical Fixing Screws are the Method of Choice for Conservative Treatment of Mandibular Fractures - Pulatova Shaxzoda Karimovna (Central Asian Journal of Medical and Natural Science, 2023)
In recent years, the orthopedic method of treating fractures of the mandible, along with traditional methods for the purpose of interdigital fixation, has seen the introduction into practice of using cortical screws, which are orthodontic mini-implants. The advantages of using these fixing elements for maxillo-mandibular immobilization compared to dental wire splints include the absence of damaging effects on periodontal and dental tissues, improving the eating process, and facilitating proper hygiene procedures for the patient.